Exploring antenatal education content for couples in Blantyre, Malawi - Maria Chifuniro Chikalipo; Ellen Mbweza Chirwa; Adamson Sinjani Muula (BMC, 2018)
Abstract Background Despite advocating for male involvement in antenatal education, there is unmet need for antenatal education information for expectant couples. The objective of this study was to gain a deeper understanding of the education content for couples during antenatal education sessions in Malawi. This is needed for the development of a tailor-made curriculum for couple antenatal education in the country, later to be tested for acceptability, feasibility and effectiveness. Methods An exploratory cross sectional descriptive study using a qualitative approach was conducted in semi-urban areas of Blantyre District in Malawi from February to August 2016. We conducted four focus group discussions (FGDs) among men and women independently. We also conducted one focus group discussion with nurses/ midwives, 13 key informant interviews whose participants were drawn from both health-related and non-health related institutions; 10 in-depth interviews with couples and 10 separate in-depth interviews with men who had attended antenatal clinics before with their spouses. All the interviews were audiotaped, transcribed verbatim and translated from Chichewa, the local language, into English. We managed data with NVivo 10.0 and used the thematic content approach as a guide for analysis. Results We identified one overarching theme: couple antenatal education information needs. The theme had three subthemes which were identified based on the three domains of the maternity cycle which are pregnancy, labour and delivery and postpartum period. Preferred topics were; description of pregnancy, care of pregnant women, role of men during perinatal period, family life birth preparedness and complication readiness plan, coitus during pregnancy and after delivery, childbirth and baby care. Conclusion Antenatal education is a potential platform to disseminate information and discuss with male partners the childbearing period and early parenting. Hence, if both men and women were to participate in antenatal education, their information needs should be prioritized. Men and women had similar choices of topics to be taught during couple antenatal education, with some minor variations.